2017
DOI: 10.21037/atm.2017.01.27
|View full text |Cite
|
Sign up to set email alerts
|

Development and use of a non-biomaterial model for hands-on training of endoscopic procedures

Abstract: Background: Endoscopic submucosal dissection (ESD) and peroral endoscopic myotomy (POEM) are recently developed techniques that have the potential to significantly improve clinical outcomes. However, training opportunities on these techniques remain limited. To address this issue, we developed a novel ex-vivo ESD/POEM training model. Our aim in this paper is to describe the model and provide preliminary evidence of promising feasibility to improve access to ESD/POEM training. Methods:The model was developed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Thus, we considered that this model could duplicate the actual gastric ESD in terms of the procedure speed in each location. Sato et al and Chen et al have reported the feasibility of ESD training models using non-animal subjects 9 10 . The model that uses non-animal subjects can be trained to be effective for ESD in any facility equipped for endoscopy, without requiring endoscopic units specialized for animal use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we considered that this model could duplicate the actual gastric ESD in terms of the procedure speed in each location. Sato et al and Chen et al have reported the feasibility of ESD training models using non-animal subjects 9 10 . The model that uses non-animal subjects can be trained to be effective for ESD in any facility equipped for endoscopy, without requiring endoscopic units specialized for animal use.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of the muscle layer also allows ESD training to be performed with caution with respect to muscle layer damage and perforation during submucosal dissection. This setting frame enables ESD in various lesion ▶ ▪ Dissection time 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) sites in the stomach by adjusting the angle of the seat position, distance between the cardia and the seat, angle of the cardia, and a spatula that imitates the greater curvature of the stomach. Therefore, the feeling of the scope's movement for each location is reproduced, and this makes it possible to be used for training while considering ESD strategies for each location.…”
Section: Discussionmentioning
confidence: 99%
“…The satisfaction rate was 100%, and the feasibility rate was 96.4%, indicating that EndoGel may be an effective endoscopy education tool. 59 …”
Section: Classification and Characteristics Of Endoscopic Training Si...mentioning
confidence: 99%
“…Recently, a new arti cial ESD simulator, Endogel (Sunarrow, Japan), was developed for ESD/ Peroral Endoscopic Myotomy (POEM) training [7,10]. Endogel is a composite plate laminated with three different types of polyvinyl alcohol hydrogel (PVA-H) sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of PVA-H sheets can be laminated with different elasticity. It is possible to simulate procedures such as mucosal incision, submucosal dissection, and muscle layer myotomy with PVA-H sheets mimicking the mucosa and submucosa [10]. However, there are some limitations to the Endogel.…”
Section: Introductionmentioning
confidence: 99%